Resiliency of Investment Climate in East Java on Labor Supply Shock and Quality Of Infrastructure - Hudaifah, Ahmad; Bambang Tutuko; Andi Zulfikar Darussalam (Universitas Airlangga, 2018)
In this study by taking the East Java region as a case study, the research will focus on the resilience of the investment climate on labor fluctuations and the deterioration of infrastructure quality. The data used are at district and city level in East Java starting from year 2007 until year 2014 which is yearly. Dependent variable in this research is total investment (INVESTMENT) that enters into districts and cities in East Java in the form of foreign direct investment (PMA) and domestics investment (PMDN), while the independent variable is divided into two categories namely labor supply shock and infrastructure quality. To represent employment conditions, several independent variable were selected namely human development index (HDI), labor force participation rate (LFPR), and district / municipal minimum wage (UMK). The other independent variables representing the quality condition of the infrastructure consisted of good road length (ROAD), power supply electricity (electricity) and government expenditure on infrastructure (GMODAL). By using panel data regression analysis in 38 districts in East Java, it can be concluded that the coefficient of UMK that contradicts with the theory can be explained from the phenomenon of data where, the minimum wage increase of city districts start 2007 to 2013 slightly has impact on the total investment value. On the other hand, infrastructure variables such as roads, electricity and allocation of government funds do not significantly affect the value of investment in East Java. Keywords: Data Panel Regression, Fixed Effect Model, Minimum Wage and Infrastructure.